September 11 in History : A Watershed Moment? - Dudziak, Mary L., 1956- (Book collections on Project MUSE., 2003)
Arguing that, despite overheated rhetoric at the time, 9/11 did not "change everything," the contributors place this tragedy in its essential historical context.